1998
DOI: 10.1046/j.1471-4159.1998.71062638.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Treatment with Morphine Increases Diazepam Binding Inhibitor mRNA in Mouse Brain

Abstract: Effects of acute and chronic morphine treatment on the expression of diazepam binding inhibitor (DBI) mRNA in the mouse brain were examined. Cerebral DBI mRNA expression significantly increased in morphine‐dependent mice, and this increase is more remarkable in morphine‐withdrawn mice, whereas a single administration of morphine (50 mg/kg) produced no changes in the expression. Simultaneous administration of naloxone (3 mg/kg) with morphine completely abolished the increase in cerebral DBI mRNA expression obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
4
11
0
Order By: Relevance
“…Mice with morphine physical dependency were prepared according to the previous methods with a minor modification (21,22). Mice were administered morphine twice a day (09:00 and 21:00 around the clock) with daily increasing doses over a period for 5 days.…”
Section: Chronic Morphine Treatmentmentioning
confidence: 99%
“…Mice with morphine physical dependency were prepared according to the previous methods with a minor modification (21,22). Mice were administered morphine twice a day (09:00 and 21:00 around the clock) with daily increasing doses over a period for 5 days.…”
Section: Chronic Morphine Treatmentmentioning
confidence: 99%
“…In socially isolated mice, DBI mRNA expression in the hypothalamus was found to be significantly less than in grouphoused animals [Dong et al, 1999]. Cerebral DBI mRNA expression also was increased in morphine-dependent mice treated with naloxone to evoke morphine withdrawal anxiety-like symptoms of jumping, ptosis, tremor, diarrhea, and weight loss [Katsura et al, 1998]. …”
Section: Dbi/pbr and Behaviormentioning
confidence: 99%
“…Although these data mentioned above raise a possibility that the increased cerebral DBI expression in the brain of mouse chronically treated with morphine (Katsura et al, 1998a) may be mediated via enhanced L-type HVCCs, there have been no data on functional relationship between morphine-induced increase of DBI expression and changes in L-type HVCCs. Life Sciences 80 (2006) 166 -172 www.elsevier.com/locate/lifescie…”
Section: Introductionmentioning
confidence: 97%
“…Diazepam binding inhibitor (DBI) is an endogenous anxiogenic polypeptide co-localized with GABA in synaptic vesicles in GABAergic neurons (Guidotti et al, 1983;Shoyab et al, 1986), and is supposed to partially participate in fear and anxiety observed as withdrawal symptoms in patients with physical dependence to drugs of abuse such as ethanol and nicotine (O'Brien, 2001;Ohkuma et al, 2001b), because DBI and its mRNA expressions in the animal brains significantly increased under the conditions of morphine-, ethanol-and nicotine-induced physical dependence (Katsura et al, 1995a(Katsura et al, , 1998aOhkuma et al, 2001b). Moreover, psychological stress significantly up-regulates DBI mRNA expression when examined using a communication box (Katsura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%